A Review of Composition–Structure–Function Properties and Tissue Engineering Strategies of Articular Cartilage: Compare Condyle Process and Knee Joint. Issue 10 (7th April 2022) - Liu, Nian; Zhang, Huabo; Ni, Xingyu; Liu, Tiancheng; Jiang, Nan
Abstract : Extensive researches in recent decades have confirmed the importance of condylar cartilage and tibial plateau cartilage in regarding their functions in joints. Although the two cartilages are in an anatomically similar environment and have some resemblances in clinical studies of osteoarthritis, the existing studies lack a cross‐sectional comparison of these two cartilage parts. Therefore, herein, the similarities and differences between the two in terms of compositions, structure, biomechanics, and tissue‐engineering strategies are horizontally compared. Recent studies on these aspects are included in this review, in which the focus and deficiency of the researches are concluded respectively. The two cartilages are both roughly divided into four layers in terms of structure, but in the aspect of composition, there are differences in the shape and size of cells and the way in which collagen exists. The compression resistance of tibial cartilage is stronger than that of condylar cartilage, which is related to their roles in normal life and has influence in tissue engineering strategies. Investigating the contrast between the two contributes to carrying out related clinical researches. Meanwhile, due to the different emphasis, it has enlightening significance for the selection of future study. Abstract : Herein, the similarities and differences between the condylar cartilage and the tibial plateau cartilage in terms of composition, structure, biomechanical properties, and tissue engineering strategies are analyzed and concluded. Not only new ideas are provided for treatment of articular cartilage diseases of the temporomandibular joint (TMJ) and knee joint, but also the direction for future research is pointed out.